2016
DOI: 10.1007/s10453-016-9443-5
|View full text |Cite
|
Sign up to set email alerts
|

Airborne pollen and fungal spores in Garki, Abuja (North-Central Nigeria)

Abstract: The ambient atmosphere is dominated with pollen and spores, which trigger allergic reactions and diseases and impact negatively on human health. A survey of pollen and fungal spores constituents of the atmosphere of Garki, Abuja (North-Central Nigeria) was carried out for 1 year (June 1, 2011–May 31, 2012). The aim of the study was to determine the prevalence and abundance of pollen and fungal spores in the atmosphere and their relationship with meteorological parameters. Airborne samples were trapped using mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 18 publications
3
22
1
1
Order By: Relevance
“…Total pollen was found to correlate positively though not significant with current temperature and negatively with current monthly rainfall and humidity. The finding agrees with previous studies in Nigeria [24,25] who also found that airborne pollen concentration correlated positively with temperature and negatively with rainfall in the atmosphere of South-east and Northcentral Nigeria, respectively.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Total pollen was found to correlate positively though not significant with current temperature and negatively with current monthly rainfall and humidity. The finding agrees with previous studies in Nigeria [24,25] who also found that airborne pollen concentration correlated positively with temperature and negatively with rainfall in the atmosphere of South-east and Northcentral Nigeria, respectively.…”
Section: Discussionsupporting
confidence: 92%
“…On the contrary, total fungal spores count and most dominant spores correlated negatively, though not significantly, with temperature. In a similar study, the same association between fungal spores with rainfall, relative humidity and temperature in North-central Nigeria was obtained [25].…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…For this reason, most outdoor airborne fungal spores originate from farms, forest stands and decomposing plant matter [45]. The marked incidence of these fungi and their impact on human health has been studied in different parts of the world [46][47][48][49]. Moulds are common aeroallergens, and Cladosporium is considered to be among the most prevalent [50].…”
Section: Discussionmentioning
confidence: 99%